Enhancing Public Involvement through Digital PR Strategies - Rouabehia, Meriem (Journal of Ecohumanism, 2025)
This study falls within the framework of academic efforts aimed at exploring the relationship between digital transformation and the activation of community participation. It does so by examining the extent to which digital public relations mechanisms are used to establish effective communication between institutions and their audiences through modern digital media. The “Sonelgaz” company in Guelma was selected as the study field, as a public service institution, to monitor the reality of digital public relations practices and their impact on enhancing audience interaction and responsiveness. To achieve the study’s objectives, a questionnaire was employed as the primary tool for collecting quantitative data due to its ability to capture respondent opinions accurately. Additionally, observation was used to monitor behavioural and communicative aspects that cannot be quantitatively measured. These tools were directed at a purposive sample of the institution’s officials due to their direct relation to the research topic, in addition to a random sample of citizens dealing with the institution, to capture the perspectives of both sides regarding digital transformation and the level of community participation through public relations channels. Upon completing the field study and analysing the data, the results revealed weak community participation in the institution’s initiatives, indicating the limited effectiveness of current digital channels in attracting and motivating the public. It also highlighted the absence of clear mechanisms to measure the impact of digital public relations campaigns on enhancing community participation.